The end of King Jehoiakim: the afterlife of a problem - Begg, Christopher (Journal for semitics, 1996)
Recently, E J Smit has surveyed the Biblical indications concerning the circumstances surrounding the end of Jehoiakim's reign (2 Kg 24:6; 2 Chr 36:6; Jr 22:19; 36:30). Smit further proposes a historical reconstruction, according to which Jehoiakim met a violent death in the context of a Babylonian attack and was denied a proper burial. The present article extends the discussion by examining the statements of Josephus, Rabbinic tradition, and Patristic commentators concerning Jehoiakim's end. It is noted that in this later material one finds explicit statements about Jehoiakim's being put to death as Smit posits, but this is said nowhere in the Biblical witnesses.